Controlling Chemical Waves by Transforming Transient Mass Transfer (Adv. Theory Simul. 3/2022). Issue 3 (10th March 2022) - Zhang, Zeren; Xu, Liujun; Huang, Jiping
Abstract : Controlling Chemical Waves Transient mass transfers like chemical waves can be manipulated according to the optimized‐transformation transient‐mass‐transfer theory. In article 2100375, Zhang, Xu and Huang design and evaluate a cloak, concentrator, rotator, and separator for chemical waves. The results provided different insights into advanced manipulation of chemical waves associated with biochemical reactions and promoted potential applications for transient mass diffusion.